MEANINGFUL PARTICIPATION IN THE PROCESS OF FORMATION LOCAL REGULATION - Natama Hasibuan, Solihin; NAM Sihombing, Eka; Afnila, Afnila (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study is based on the principle of meaningful community participation in the process of forming regional regulations, in realizing constitutional rights to obtain equal opportunities at each stage of the process of forming regional regulations. The mandate of the Constitutional Court (MK) Decision Number 91/PUU-XVIII/2020 emphasizes that community participation must be interpreted as the right to be heard, the right to be considered and the right to receive an explanation or answer to the opinion given (right to be explained). This authority is still found to be limited by the community in obtaining information about whether their opinions are rejected or accepted. In fact, this authority is an interpretation of the sovereignty of the people which must be manifested at every level of regional law formation. It shows the need for affirmation of comprehensive and representative meaningful community participation through regional regulations themselves. Collectively, meaningful community participation in the process of forming regions is only understood normatively, which results in the interpretation of meaningful community participation in the process of forming regional regulations only as a formal requirement. The formulation of the problem in this study is (1) How is the regulation of meaningful community participation in the process of forming regional regulations?, (2) What is the mechanism of meaningful community participation in the process of forming regional regulations?, (3) How is the implementation of meaningful community participation in the process of forming regional regulations?. This study uses a normative legal method with a conceptual approach, statue approach and case approach. This paper concludes that the implementation of meaningful community participation in the process of forming regional regulations has not been systematically arranged by the Regional People's Representative Council (DPRD) over the authority of meaningful communities in the process of forming regional regulations. In Langkat Regency, the implementation of meaningful community participation is only at the recess and public consultation stages or public hearings (RDPU). This paper recommends that the DPRD form a regional regulation in absorbing meaningful community participation. By emphasizing the definition of regional community involvement in a more meaningful direction, and reorganizing the systematics of representative regional institutions in accommodating meaningful community participation in the stages of the process of forming regional regulations.